Inflammatory breast cancer appearance at presentation is associated with overall survival. (30th July 2021) - Balema, Wintana; Liu, Diane; Shen, Yu; El‐Zein, Randa; Debeb, Bisrat G.; Kai, Megumi; Overmoyer, Beth; Miller, Kathy D.; Le‐Petross, Huong T.; Ueno, Naoto T.; Woodward, Wendy A.
Abstract: Background: Inflammatory breast cancer (IBC) is a clinical diagnosis. Here, we examined the association of a "classic" triad of clinical signs, swollen involved breast, nipple change, and diffuse skin change, with overall survival (OS). Method: Breast medical photographs from patients enrolled on a prospective IBC registry were scored by two independent reviewers as classic (triad above), not classic, and difficult to assign. Chi‐squared test, Fisher's exact test, and Wilcoxon rank‐sum test were used to assess differences between patient groups. Kaplan–Meier estimates and the log‐rank test and Cox proportional hazard regression were used to assess the OS. Results: We analyzed 245 IBC patients with median age 54 (range 26–81), M0 versus M1 status (157 and 88 patients, respectively). The classic triad was significantly associated with smoking, post‐menopausal status, and metastatic disease at presentation ( p = 0.002, 0.013, and 0.035, respectively). Ten‐year actuarial OS for not classic and difficult to assign were not significantly different and were grouped for further analyses. Ten‐year OS was 29.7% among patients with the classic sign triad versus 57.2% for non‐classic ( p < 0.0001). The multivariate Cox regression model adjusting for clinical staging ( p < 0.0001) and TNBC status (<0.0001) demonstrated classic presentation score significantly associated with poorer OS time (HR 2.6, 95% CI 1.7–3.9, p < 0.0001). Conclusions: A triad of classic IBC signs independently predicted OS in patients diagnosed with IBC. Further work is warranted to understand the biology related to clinical signs and further extend the understanding of physical examination findings in IBC. Abstract : Inflammatory breast cancer (IBC) is a clinical diagnosis. Here, we examined the association of a "classic" triad of clinical signs, swollen involved breast, nipple change, and diffuse skin change, with overall survival (OS). Our study concluded for the first time that a triad of classic IBC signs independently predicted OS in patients diagnosed with IBC.